THE INFLUENCE OF USING PROBLEM-BASED LEARNING ON STUDENTS’ WRITING ABILITY IN ANALYTICAL EXPOSITION TEXT IN THE ELEVENTH GRADE OF SMA KEMALA BHAYANGKARI KOTABUMI IN ACADEMIC YEAR 2025/2026 - Marthalia Farmadeaty; Elis Susanti; Yuli Yantika; Reni Erawati; Ega Wardani; Yolanda; Yusuf Nurparit (Universitas Muhammadiyah Kotabumi, 2023)
Students’ writing ability were still relatively low, characterized by difficulties in developing ideas, limited vocabulary mastery, and the use of inappropriate language structures. The Problem-Based Learning (PBL) method was believed to improve these ability because it emphasized problem-solving, encouraged active student involvement, and promoted critical thinking. Then the purpose of this study was to determine the influence of using problem-based learning on students’ writing abilities. This study used experimental research with a quasi-experimental design. The population in this study were all of the eleventh grade at SMA Kemala Bhayangkari Kotabumi with a total of 188 students, the sample taken in this study was class XI.5 as the experimental class and class XI.6 as the control class, with a total of 59 students. In the experimental class group, learning was given using the problem-based learning method, but for the control class group was taught by using the usual method applied by the teacher. The instrument use in this study was an analytical exposition text writing test. Data collection was carried out by means of a pretest then posttest, after which the data was analyzed using t-test. The results of the study showed that the tobserved was 4,636 with ttable 2,0027, indicating that the tobserved was greater than ttable. It means that the use of problem-based learning has an influence on the ability to write analytical exposition text. Teachers were encouraged to apply the Problem- Based Learning (PBL) method in writing instruction to improve students’ writing ability. Future studies were suggested to examine its effectiveness in different contexts.